Pemberdayaan Masyarakat Terhadap Peningkatan UMKM Waroeng Aidina Di Sektor Ekonomi - Thoriq Firmansyah Rachman; Daisy Marthina Rosyanti (Sekolah Tinggi Ilmu Ekonomi Trianandra, 2023)
In terms of location, Rungkut Kidul District has high potential where there are many MSMEs who live and sell there. Through community empowerment towards increasing MSMEs, it seeks to create improvements in the economic sector. However, local people lack the necessary knowledge to expand consumer reach, attract consumers to choose their products and increase sales figures. And for the time being they only sell from neighbor to neighbor. Therefore the answer to this problem is to equip MSMEs on how to expand sales and get consumers to choose their products. With the aim of empowering the community to master technology, marketing management and attracting the attention of consumers, this has been achieved through community service activities. Several approaches have been taken to increase MSMEs in the economic sector as follows: 1) outreach and FGD (Forum Group Discussion); 2) trainingDigital Marketing, 3) mentoring, this aims so that after the community empowerment program is completed, this increase in the economic sector is maintained in the future. The solution can be done through socialization programs and FGD (Forum Group Discussion) to find out what problems are experienced by these MSMEs, especially Waroeng Aidina. Conducting Digital Marketing training is the next step where to expand enthusiasts or consumers. These final results can include various improvements in the economic sector as well as an increase in MSMEs in the Rungkut Kidul sub-district area.